2005
DOI: 10.1186/1471-2458-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among Bam earthquake survivors in Iran: a population-based study

Abstract: Background: An earthquake measuring 6.3 on the Richter scale struck the city of Bam in Iran on the 26th of December 2003 at 5.26 A.M. It was devastating, and left over 40,000 dead and around 30,000 injured. The profound tragedy of thousands killed has caused emotional and psychological trauma for tens of thousands of people who have survived. A study was carried out to assess psychological distress among Bam earthquake survivors and factors associated with severe mental health in those who survived the tragedy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
99
3
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 18 publications
10
99
3
5
Order By: Relevance
“…Within the context of this cultural background, full-time housewives may experience more psychological stress when a natural disaster, such as a large earthquake occurs. A high prevalence of psychological distress in unemployed people was also reported after the 2003 Bam Iranian earthquake [16]. This finding may be due, in part, to financial losses and cost burdens from house damage that adversely affect psychological health [11,17,18].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Within the context of this cultural background, full-time housewives may experience more psychological stress when a natural disaster, such as a large earthquake occurs. A high prevalence of psychological distress in unemployed people was also reported after the 2003 Bam Iranian earthquake [16]. This finding may be due, in part, to financial losses and cost burdens from house damage that adversely affect psychological health [11,17,18].…”
Section: Discussionmentioning
confidence: 82%
“…Reports of associations between gender and post-earthquake psychological distress have been inconsistent [13,16,17]. In a study of Turkish earthquake survivors in which 82% of the women were full-time housewives, Başoglu et al [13] suggested that women tend to have dependent roles in traditional societies, such as the Turkish society, increasing their risk for emotional repercussions following a disaster.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bam earthquake in Iran on the 26 th December 2013 showed 58% respondent had severe mental health problems. (Montazeri et al, 2005) Similarly, 8 month after the 2008 Wenchuan earthquake in china showed the depression was 35.7%. (Qu et al, 2014) Another study which was conducted in 2010 showed the anxiety and depression symptoms 43.8 % and 38.6% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, few have examined the effects of disaster-related stress on perinatal women [6][7][8][9]. The findings of these earlier studies suggest that prenatal stress caused by natural and man-made disasters may result in minor psychiatric distress [3,4], low birth weight [7], preterm delivery [6,10], smaller head circumference [6,7], skewed sex ratios [9], retardation of fetal brain development [11], and reduction of breast milk supply [8]. It also would seem that pregnant women are more susceptible to the effects of stress in the first trimester than in the second and third trimesters [6,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have addressed the various health problems caused by devastating earthquakes [1][2][3][4][5]. Of these, few have examined the effects of disaster-related stress on perinatal women [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%